PENDAMPINGAN MANAJEMEN SUMBER DAYA MANUSIA DI MADRASAH IBTIDAIYAH AL-AZHAR AJUNG JEMBER UNTUK MENINGKATKAN MUTU PENDIDIKAN - Khotibul Umam Khotibul Umam ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2022)
Assistance with human resource management at madrasah ibtidaiyah is one of the efforts to improve the quality of education. This is because Human Resources are an important factor in the success of an educational institution. Through human resource assistance, madrasas can develop the competence of teachers and other education personnel, so that they can provide quality education services to students. The quality of education is one indicator of the success of a madrasah. The quality of education can be measured from various aspects, including student learning outcomes, the quality of the learning process, and the quality of facilities and infrastructure. Good human resource management can influence the quality of madrasa education. Quality human resources will be able to provide quality learning to students. Competent human resources will be able to develop curriculum and learning methods that suit student needs. Motivated human resources will be able to create a conducive learning environment for students. Based on the results of research that has been carried out, good human resource management can improve the quality of education in madrasah ibtidaiyah. This research shows that madrasas that have good human resource management have higher student learning outcomes, better quality of the learning process, and better quality of facilities and infrastructure.